Evaluation of Nursing Service Management Model applied in hospitals managed by social health organization - Elizabeth Akemi Nishio; Maria Lucia Alves Pereira Cardoso; Maria Elisabete Salvador; Maria D'Innocenzo
ABSTRACT Objective: Evaluate the Hospital Nursing Service Management Model from the perspective of nurses from hospitals managed by social health organization, considering the type and dimensions of the model. Methods: This is an exploratory, cross-sectional study with a quantitative approach; census population. The evaluation was conducted in 15 hospitals based on the Index of Professional Nursing Governance, including the descriptive analysis of the k-means method and multiple linear regression to score the instrument. Data collection was performed online, stored in REDCap®. Results: Of 1,523 invited, 680 (44.6%) accepted and 518 (34.1%) completed the questionnaire. With a general average of 184.3 points, 12 hospitals indicated shared; and 3 (20%), traditional governance (average of 165.7 points). Conclusion: Managers presented a lower perception of shared governance with professionals without a management function. The type of function and time of activity at the institution influenced the results. The present model is hybrid, in the transition process from the traditional to corporate.